Analysis of The Urgency of Boarding School Accounting for Public Accountants in The Modern Era - Purwati (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
Islamic boarding schools (Pesantren) as educational institutions play a strategic role in shaping the moral and character of the nation. In the modern era, financial management in Islamic boarding schools has become increasingly complex due to the growth of funding sources, as well as the transparency and accountability expected by various stakeholders. Furthermore, the sustainability and credibility of Islamic boarding schools are significantly influenced by their ability to prepare financial reports in accordance with Sharia principles and applicable accounting standards. This article aims to analyze the urgency of implementing Islamic boarding school accounting and the role of public accountants in supporting good governance. The research method used is a literature review and qualitative analysis. The findings indicate that implementing Sharia-based accounting, relevant to the unique characteristics of Islamic boarding schools, is crucial to meeting the demands for transparency and accountability. This study recommends collaboration between Islamic boarding schools and public accountants to develop specific Islamic boarding school accounting standards and enhance Islamic boarding school's financial management capacity. Keywords: I, , Public Accountant